(3agQS eDdaGJ GdSLGYis - (3GdSLGYj , CMeO Hf CMeO Hf eMeO GdSLGYj GdHOQGhj GdGRgQj, TgGH GdOjf,J (B1197 (3g` s
(3ChdgG (B:s
(3MeOkG def NU ef fTC ef YHGOg HEbGeI GdTQjYI GdeMeOjI gPg QSGdI dWjaI deDdaGJ TjNfG GdEeGe CMeO GdSLGYi s
(3BNQgG (B:s
(3JeJ GdeDdaGJ GdcGedI s
(3Yf fSNI HNW JdejP ddeDdas
(3jdjgG agQS HeG hbag GdSLGYi ef GdcJH Ydi WdHI GdYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B93 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B154s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3agGQS hecJHGJs